A SYSTEMATIC REVIEW INVESTIGATING THE EFFECTS OF FAMILY INVOLVEMENT IN THE CARE OF THE ADOLESCENT DIABETIC - Hamilton, Eleanor Jane (2013)
Background This study investigates the effects of family involvement in the care of the adolescent diabetic. Diabetes mellitus affects people and their families worldwide. Managing diabetes requires a daily execution of complex and demanding health behaviours, which becomes more complicated when coupled with the critical growth period of adolescence. Diabetic adolescents are a vulnerable group of individuals that commonly show poor glycaemic control. It is therefore important to understand how adolescents can be effectively supported in attaining good glycaemic control before they reach adulthood. Methods A systematic review was undertaken to review interventions that encourage family involvement in the care of the diabetic adolescent, and determine whether family involvement was a factor in improving glycaemic control. Electronic databases were searched using search terms determined using PICOS (population, intervention, comparison, outcomes, and study design), and additional studies were identified using reference lists from selected studies. Studies were put through a systematic selection process using inclusion and exclusion criteria before data extraction. Finally, data was extracted and critically analysed using a quality assessment tool. Results The systematic process identified eight randomised controlled trials that examined family involvement in the care of the diabetic adolescent, these were then analysed to identify themes and discussed. The themes identified were; glycaemic control, treatment adherence, teamwork/ family involvement, and diabetes related family conflict. The review demonstrated that increased family involvement in the care of the diabetic adolescent improves glycaemic control. Family involvement also improved treatment adherence, however did show links to increased diabetes-related family conflict. Conclusion The review states that sustained parental involvement in diabetes care (from childhood age 0-10 through adolescence age 10-19) should be encouraged because it does improve glycaemic control. Families can be encouraged to remain involved in the care of their children’s diabetes through to adolescence during clinic visits, which would not call for additional resources.